Ion cyclotron emission in NBI-heated plasmas in the TUMAN-3M tokamak. (22nd June 2018) - Askinazi, L.G.; Belokurov, A.A.; Gin, D.B.; Kornev, V.A.; Lebedev, S.V.; Shevelev, A.E.; Tukachinsky, A.S.; Zhubr, N.A.
Abstract: Ion cyclotron emission (ICE) observation in neutral beam injection (NBI)-heated plasma in the TUMAN-3M tokamak is reported. Experiments were performed in deuterium or hydrogen target plasmas, with the neutral heating beam consisting of 60% deuterium and 40% hydrogen atoms accelerated up to 16 keV. High-frequency internal magnetic probes were used as a diagnostic tool for ICE detection. In deuterium plasmas, emission with 13 MHz frequency was observed, with 1–2 ms delay after the NBI pulse front; this frequency corresponds approximately to fundamental ion cyclotron (IC) resonance for hydrogen near the magnetic axis. In hydrogen plasmas, ICE with frequency 7 MHz was observed. In both cases, the observed frequency scales as IC resonance of minority ions. In deuterium plasmas, the hydrogen minority ICE spectral line was found to consist of several narrow (width 50 kHz) spectral components, typically three or more, with different spacing (of the order of 50–200 kHz), and temporal dynamics in synchronicity with sawtooth oscillations. The ICE with the frequency corresponding to IC resonance for majority ions was also observed in several hydrogen and deuterium discharges. Theoretical models developed for the explanation of NBI ICE on other tokamaks are not easily applicable for the phenomena observed on the TUMAN-3M. In pure ohmically heated deuterium and hydrogen plasmas, i.e. in the absence of fast ions, a weak ICE was also observed, with frequency scaling as IC resonance condition in close proximity to the probe location.